The relationship between value preference and gender in future teachers in Chilean higher education - Saavedra, Rodrigo Arellano; Ranjan, Ranjeeva; Philominraj, Andrew; Urzua, Claudio Andres Cerón (Nurture, 2024)
Purpose: This study aimed to examine the values associated with pedagogical training and the differences in value preferences among students based on gender in institutions in the central-southern area of Chile. The objective of the research was to analyse the values associated with pedagogical training and the differences in value preferences according to the gender of students in universities in the central-southern area of Chile. Design/Methodology/Approach: The methodology used in the study is quantitative and descriptive. The study sample consisted of 437 students from Chilean universities. The information was collected using a standardized instrument called the adapted values test. Findings: The results indicated a clear preponderance in the categories of moral, ecological, individual, affective and bodily values. Political and moral values were not particularly taken into consideration. Significant differences were found concerning gender. Females achieve higher mean scores than males except in instrumental values. Conclusions: The results show the educational needs of future teachers in terms of axiological training from a gender perspective. Practical Implications: Identifying and analyzing the axiological structure of students and teachers in private and public universities in Chile will allow proposing value education in the curricular plans of future teachers. On the other hand, the values transmitted by teachers are different which implies the development of pedagogical training programs that strengthen gender differences as an instance of cultural equity. Contribution to the Literature: This research underscores the importance of value education in teacher training programs and explains how university students perceive them.